Causal relationships between gut microbiota, immune cell, and Henoch-Schönlein Purpura: a two-step, two-sample Mendelian randomization study - Liang, Tian; Shi, Huijun; Cui, Han; Cui, Yaqi; Zhao, Ziwei; Wang, Yue; Shi, Dandan; Tian, Peichao (Frontiers in Immunology, 2024)
Background: Regulating the immune system is a crucial measure of gut microbiota (GM) that influences the development of diseases. The causal role of GM on Henoch-Schönlein Purpura (HSP) and whether it can be mediated by immune cells is still unknown.Methods: We performed a two-sample Mendelian randomization study using an inverse variance weighted (IVW) method to examine the causal role of GM on HSP and the mediation effect of immune cells between the association of GM and HSP.Results: We demonstrated the causal relationships between 14 axas and 6 pathways with HSP. Additionally, we identified 9 immune cell characteristics associated with HSP. Importantly, through mediation MR analysis, we identified several immune cell characteristics that mediate the impact of GM on HSP. For instance, Genus_Blautia affects HSP via Monocyte (HLA DR on CD14+ CD16monocyte) and Monocyte (HLA DR on monocyte). The proportion of mediation effects further elucidated the complex dynamics between GM exposure, immune markers, and their combined impact on HSP.The study suggested a causal relationship between GM and HSP, which may be mediated by immune cells.